2021
DOI: 10.1007/s00784-021-04024-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of diagnostic methods for occlusal surface caries

Abstract: Aim This systematic review and meta-analysis aimed to assess the diagnostic performance of commonly used methods for occlusal caries diagnostics, such as visual examination (VE), bitewing radiography (BW) and laser fluorescence (LF), in relation to their ability to detect (dentin) caries under clinical and laboratory conditions. Materials and methods A systematic search of the literature was performed to identify studies meeting the inclusion criteria usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…All the images were labeled by an experienced examiner (JK, >20 y of clinical practice and scientific experience), who was also aware of the patients’ history and overall dental status, into the following categories: 0, surfaces with no caries; 1, surfaces with signsof a noncavitated caries lesion (first signs, established lesion, localized enamel breakdown); and 2, surfaces with caries-related cavitation (dentin exposure, large cavity). Both caries thresholds are of clinical relevance and also commonly used in caries diagnostic studies ( Schwendicke, Splieth, et al 2019 ; Kapor et al 2021 ). Each diagnostic decision—1 per image—served as a reference standard for cyclic training and repeated evaluation of the deep learning–based CNN.…”
Section: Methodsmentioning
confidence: 99%
“…All the images were labeled by an experienced examiner (JK, >20 y of clinical practice and scientific experience), who was also aware of the patients’ history and overall dental status, into the following categories: 0, surfaces with no caries; 1, surfaces with signsof a noncavitated caries lesion (first signs, established lesion, localized enamel breakdown); and 2, surfaces with caries-related cavitation (dentin exposure, large cavity). Both caries thresholds are of clinical relevance and also commonly used in caries diagnostic studies ( Schwendicke, Splieth, et al 2019 ; Kapor et al 2021 ). Each diagnostic decision—1 per image—served as a reference standard for cyclic training and repeated evaluation of the deep learning–based CNN.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the previous systematic reviews and meta-analyses about technologies in caries detection have focused on traditional and commonly used non-traditional technologies [25][26][27]29,30]. They did not address or study new methods, such as the Midwest Caries I.D.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging technologies in this review had few identified studies that met the inclusion criteria. Although recent systematic reviews and meta-analyses overlooked these technologies probably due to the low number of available studies [29,30], their diagnostic potential should be acknowledged. We systematically identified these studies, collected the performance data, synthesized them and then put them in context, irrespective of the reports' number; this contribution might help future investigators to build up on existing body of evidence.…”
Section: Newly Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of diagnostic approaches are available to assist clinicians in caries detection and diagnosis [ 7 , 8 ]. Studies evaluating the accuracy of these approaches, however, primarily focus on coronally located caries lesions.…”
Section: Introductionmentioning
confidence: 99%